2023
DOI: 10.1177/10760296231159113
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume as a Predictor of Coronary Artery Disease Severity and its Association With Coronary Artery Calcification

Abstract: Coronary calcium score (CCS) is a highly sensitive marker for estimating coronary artery calcification (CAC) and detecting coronary artery disease (CAD). Mean platelet volume (MPV (is a platelet indicator that represent platelet stimulation and production. The aim of the current study was to examine the association between MPV values and CAC. We examined 290 patients who underwent coronary computerized tomography (CT) exam between the years 2017 and 2020 in a tertiary care medical center. Only patients evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Compared with other plasma or serumbased biomarkers and various imaging modalities for prediction, MPV allows the use of complete blood count (CBC) tests in limited healthcare resources, which is simpler and less costly, reducing the healthcare burden on pregnant women in low-and middle-income areas. It is demonstrated that MPV can be used as a predictor of the severity and prognosis of cardiovascular disease (18,19) and infectious diseases (20), while increased MPV is associated with the occurrence and severity of gestational diabetes (21) and intrahepatic cholestasis (22).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other plasma or serumbased biomarkers and various imaging modalities for prediction, MPV allows the use of complete blood count (CBC) tests in limited healthcare resources, which is simpler and less costly, reducing the healthcare burden on pregnant women in low-and middle-income areas. It is demonstrated that MPV can be used as a predictor of the severity and prognosis of cardiovascular disease (18,19) and infectious diseases (20), while increased MPV is associated with the occurrence and severity of gestational diabetes (21) and intrahepatic cholestasis (22).…”
Section: Introductionmentioning
confidence: 99%